Hubungan Prenatal Yoga Terhadap Kecemasan Ibu Hamil Trimester III Di TPMB Tri Imawati S.ST., Bdn Kota Metro - Fadilah, Intan; Kurniasari, Devi; Zarma, Zarma (MIDWIFERY JOURNAL, 2025)
Anxiety in pregnant women in the third trimester is a psychological problem that often occurs before childbirth. High levels of anxiety can have a negative impact on the condition of the mother and fetus. Prenatal yoga is a non-pharmacological intervention that has been proven effective in reducing anxiety during pregnancy.This study aims to determine the relationship between prenatal yoga and anxiety levels in pregnant women in their third trimester at TPMB Tri Imawati SST., Bdn Metro City. This study uses a quantitative approach with a cross-sectional design. The sample consisted of 20 pregnant women in their third trimester who were selected using  accidental  sampling.  Data  were  collected  using  the  Prenatal  Anxiety  Screening  Scale  (PASS) questionnaire and analyzed using the Chi-Square test.The results showed that of the 10 pregnant women who participated in prenatal yoga, the majority experienced mild anxiety and none experienced anxiety. In contrast, of the 10 pregnant women who did not participate in prenatal yoga, all experienced severe anxiety. The analysis results showed a significant relationship between prenatal yoga and anxiety levels (p < 0.05).There is a significant relationship between prenatal yoga and anxiety levels in pregnant women in their third trimester. Prenatal yoga can be used as an alternative intervention to reduce anxiety before childbirth. Keywords: Prenatal yoga, anxiety, pregnant women, third trimester ABSTRAK Kecemasan pada ibu hamil trimester III merupakan permasalahan psikologis yang sering terjadi menjelang persalinan. Tingkat kecemasan yang tinggi dapat berdampak buruk terhadap kondisi ibu dan janin. Prenatal yoga merupakan intervensi non- farmakologis yang terbukti efektif dalam mengurangi kecemasan selama kehamilan.Penelitian ini bertujuan untuk mengetahui hubungan antara prenatal yoga terhadap tingkat kecemasan pada ibu hamil  trimester  III  di  TPMB  Tri  Imawati  SST.,  Bdn  Kota  Metro.  Penelitian  ini  menggunakan  pendekatan kuantitatif  dengan  desain  cross-  sectional.  Sampel  terdiri  dari  20  ibu  hamil  trimester  III  yang  dipilih menggunakan teknik accidental sampling. Data dikumpulkan menggunakan kuesioner Prenatal Anxiety Screening Scale (PASS) dan dianalisis dengan uji Chi-Square.Hasil penelitian menunjukkan bahwa dari 10 ibu hamil yang mengikuti prenatal yoga, mayoritas mengalami kecemasan ringan dan tidak ada kecemasan. Sebaliknya, dari 10 ibu hamil yang tidak mengikuti prenatal yoga, seluruhnya mengalami kecemasan berat. Hasil analisis menunjukkan adanya hubungan yang signifikan  antara prenatal yoga dengan tingkat kecemasan (p < 0,05).Terdapat hubungan yang signifikan antara prenatal yoga dengan tingkat kecemasan pada ibu hamil trimester III. Prenatal yoga dapat dijadikan sebagai alternatif intervensi dalam menurunkan kecemasan menjelang persalinan Kata Kunci: Prenatal yoga, kecemasan, ibu hamil, trimester III